Amplification of DNA damage by a γH2AX-targeted radiopharmaceutical. - Cornelissen, B; Darbar, S; Kersemans, V; Allen, D; Falzone, N; Barbeau, J; Smart, S; Vallis, K (Elsevier, 2012)
(111)In-DTPA-anti-γH2AX-Tat, which combines an anti-γH2AX antibody with a cell-penetrating peptide, Tat, and the Auger electron-emitting radioisotope, (111)In, targets the DNA damage signalling protein, γH2AX, and has potential as a probe for imaging DNA damage in vivo. The goal of this study was to investigate whether (111)In-DTPA-anti-γH2AX-Tat labelled to high specific activity (6MBq/μg) can amplify treatment-related DNA damage for therapeutic gain.MDA-MB-468 and MDA-MB-231/H2N (231-H2N) breast cancer cells were incubated with (111)In-DTPA-anti-γH2AX-Tat (3MBq, 6MBq/μg) or a control radioimmunoconjugate, (111)In-DTPA-mIgG-Tat, and exposed to IR or bleomycin. DNA damage was studied by counting γH2AX foci and by neutral comet assay. Cytotoxicity was evaluated using clonogenic assays. (111)In-DTPA-anti-γH2AX-Tat was administered intravenously to 231-H2N-xenograft-bearing Balb/c nu/nu mice in tumor growth inhibition studies.The number of γH2AX foci was greater after exposure of cells to IR (10Gy) plus (111)In-DTPA-anti-γH2AX-Tat compared to IR alone (20.6±2.5 versus 10.4±2.3 foci/cell; P<.001).(111)In-DTPA-anti-γH2AX-Tat resulted in a reduced surviving fraction in cells co-treated with IR (4Gy) versus IR alone (5.2%±0.9% versus 47.8%±2.8%; P<.001). Similarly, bleomycin (25-200μg/mL) plus (111)In-DTPA-anti-γH2AX-Tat resulted in a lower SF compared to bleomycin alone. The combination of a single exposure to IR (10Gy) plus (111)In-DTPA-anti-γH2AX-Tat significantly decreased the growth rate of 231-H2N xenografts in vivo compared to either (111)In-DTPA-anti-γH2AX-Tat or IR alone (-0.002±0.004 versus 0.036±0.011 and 0.031±0.014mm(3)/day, respectively, P<.001).(111)In-DTPA-anti-γH2AX-Tat amplifies anticancer treatment-related DNA damage in vitro and has a potent anti-tumor effect when combined with IR in vivo.